Outcomes of job crafting among flight attendants - Karatepe, Osman M.; Eslamlou, Aram (Elsevier Sci Ltd, 2017)
Underpinned by Job Demands-Resources theory, our study proposes and tests a conceptual model that examines the outcomes of job crafting among flight attendants. Specifically, our study links job crafting, as manifested by increasing structural job resources, increasing social job resources, and increasing challenging job demands, to quitting intentions and service recovery performance through work engagement. Our study used a time-lagged design and multiple sources of data. The results from structural equation modeling reveal that job crafting fosters flight attendants' work engagement and service recovery performance. As hypothesized, work engagement alleviates quitting intentions. Consistent with our prediction, work engagement mediates the influence of job crafting on quitting intentions. Contrary to what has been hypothesized, the empirical data do not lend any support to the mediating role of work engagement in the relationship between job crafting and service recovery performance. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Flight attendants; Job crafting; Quitting intentions; Service recovery performance; Work engagement